Changes in the Social Structure of the Kalmyk Society in the Late 19th and Early 20th Century - Komandzhaev, Alexandr Narmaevich; Komandzhaev, Evgeny Alexandrovich; Batyrov, Valery Vladimirovich (International Review of Management and Marketing, 2016)
The article analyses changes in the social structure of the Kalmyk society in the late 19th – early 20th century under the influence of the reform of 1892 that abolished personal dependence of commoners from the nobility. The authors examined the reasons of adoption and the main directions of the reform of 1892 in Kalmykia, identified priority directions of social changes and established the sources of new types of Kalmykia rural population. The work is based on the extensive literary and archival material, primarily statistical. To achieve maximum objectivity, the authors frequently used averaged numerical indicators as annual statistical data greatly differed due to an imperfect data collection system and instability of the nomadic. In a number of cases to show the role of the patriarchal-tribal relations, the authors used observations of contemporaries. The article deals with the accession sources of Kalmyk new property nobility. Special attention is paid to the fact that its predominant stratum was the representatives of the commoners' stratum. The specificity of the Kalmyk society social stratification in different uluses was determined based on the statistics. The article demonstrates the scale of hired labour use in Kalmykia. The available data fully confirm significant use of hired labour in the Kalmyk livestock farms and partly in agricultural farms of Kalmykia. Thus, the new phenomena in the Kalmykia economy had an impact on the evolution of social relations in this region. Keywords: Kalmyks, social structure, nobility, commoners, hired labour, market, seasonal work. JEL Classifications: J110, J580, Z130